Belus in the Sacred History of Euhemerus - Garstad, Benjamin (My University, 2004)
Euhemerus of Messene (ﬂ. c. 300 b.c.e.) wrote a ﬁctitious narrative called the Sacred History (Hiera Anagraphe) in which he claimed to have sailed to Panchaea, an island beyond Arabia on the Ocean, and there discovered a stele on which was written the story of the time when the gods were mortal men and rulers of the whole earth. Ever since, there have been arguments over whether Euhemerus was an atheist or a revolutionary philosopher, whether he was an historian or a theologian, and whether he wrote in response to the political, or the religious reality of his day. Although the discussion of Zeus in the Sacred History is known to us only at third hand (from Eusebius’ summary of Diodorus’ rendition, and from Lactantius’ citations of Ennius’ Latin translation), it seems clear that Belus of Babylon held a place of importance in the story, and may help us to answer some of our questions in regard to Euhemerus. The narratives of Euhemerus and his followers are united by the basic theory that the gods of myth were ancient human kings and by certain consistent features, including travels throughout the world by the “gods” to encourage civilization and their own worship. In Euhemerus’ own narrative the ﬁrst item of note on Zeus’ itinerary is a visit to Belus in Babylon.
Keywords: Euhemerus of Messene; the Sacred History; Hiera Anagraphe; Panchaea; discussion of Zeus; Ennius; Belus of Babylon; Berossus; Hecataeus of Abdera